Critical Roles of Kupffer Cells in the Pathogenesis of Alcoholic Liver Disease: From Basic Science to Clinical Trials - Zeng, Tao; Zhang, Cui-Li; Xiao, Mo; Yang, Rui; Xie, Ke-Qin (Frontiers in Immunology, 2016)
Alcoholic liver disease (ALD) encompasses a spectrum of liver injury ranging from steatosis to steatohepatitis, fibrosis, and finally cirrhosis. Accumulating evidences have demonstrated that Kupffer cells (KCs) play critical roles in the pathogenesis of both chronic and acute ALD. It has become clear that alcohol exposure can result in increased hepatic translocation of gut-sourced endotoxin/lipopolysaccharide (LPS), which is a strong M1 polarization inducer of KCs. The activated KCs then produce a large amount of reactive oxygen species (ROS), proinflammatory cytokines, and chemokines, which finally lead to liver injury. The critical roles of KCs and related inflammatory cascade in the pathogenesis of ALD make it as promising targets in pharmaceutical drug developments for ALD treatment. Several drugs (such as rifaximin, pentoxifylline, infliximab, etc) have been evaluated or are under evaluation for ALD treatment in randomized clinical trials. Furthermore, screening pharmacological regulators for KCs towards M2 polarization may provide additional therapeutic agents. The combination of these potentially therapeutic drugs with hepatoprotective agents (such as zinc, melatonin, silymarin, etc) may bring encouraging results.